An Analysis Of The Implementation Of Assessment Rubrics In Evaluating Writing Creativity - Raya Gilang Safitri; Sri Marmoah; Karsono Karsono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Assessment of writing creativity in primary education often faces challenges due to subjective judgments by teachers. The use of assessment rubrics offers an objective and structured alternative for evaluating aspects of creativity such as originality, elaboration, and uniqueness. This study aims to: 1) analyse the application of assessment rubrics in assessing writing creativity, 2) evaluate the impact of using assessment rubrics on improving students' writing skills. The research method used is Systematic Literature Review (SLR) with steps of identification, selection, data extraction, and synthesis of information from various relevant scientific articles. Data sources were obtained from national and international accredited journals within the last ten years. Inclusion criteria included publications that discussed assessment rubrics, objective assessment, writing creativity, and their implementation in primary education. It can be concluded that rubrics are effective tools for assessing writing creativity, but their optimal implementation requires teacher capacity building and stronger policy support to ensure sustainability.